Arugula phytomass yield in different light environments and organic substrates (Research, Society and Development, 2022)
Dry matter accumulation in vegetables is influenced by light and mineral nutrition. In this context, the objective was to evaluate the interference of light environments and organic substrates on the phytomass yield of the Folha Larga arugula variety. The research was carried out in a greenhouse belonging to the Center for Agricultural Environmental and Biological Sciences of the Federal University of Recôncavo da Bahia, located in the city of Cruz das Almas-BA. The experimental design used was completely randomized, under a 3 x 3 factorial scheme, that is, three light environments and three types of organic substrates, with 8 replications. The light environments consisted of ChromatiNet Red and black shading meshes, both with 50% of solar irradiation, and another environment in full sun, while the substrates used were cattle manure, sheep and earthworm humus at a dose of 60 t ha-1. Subsequently, 24 plants were placed in each environment, one per pot. After 45 days of acclimatization, the following variables were evaluated: dry matter mass of leaves, stems, root, shoot, total dry matter mass and ratio between root and shoot dry matter mass. Data were submitted to analysis of variance and in terms of significance, Tukey's multiple comparison test was used at 5% probability. There were significant interactions between the sources of variation for the dry mass of leaves, stems, total and in the relation of dry mass of roots and shoots.